The regulatory effect of Xiaoyao San on glucocorticoid receptors under the condition of chronic stress - Lu, Jiandong; Fu, Lijun; Qin, Guozhong; Shi, Pengliang; Fu, Wenjun (Cellular and Molecular Biology, 2018)
In modern society, fierce competitions cause yearly increase of depression and anxiety. Xiaoyao San is a traditional Chinese medicine which relieves depression and nourishes liver. The active ingredients contain saikoside A, saikoside C, saikoside D, ferulic acid, ligustilide, Atractylenolide I, Atractylenolide II, Atractylenolide â…¢, paeoniflorin, Albiflorin, liquiritin, glycyrrhizic acid and pachymic acid. In stress condition, glucocorticoid receptors participate in the hypothalamus-pituitarium-adrenal gland (HPA) axis to regulate the balance of organism. In response to stress, the HPA axis (hypothalamus-pituitarium-adrenal gland) is activated and the levels of glucocorticoid (GC) and catecholamine (CA) are increased to enhance neuroendocrine reactions. Chronic stress activates HPA axis and sustaining increase of GC, reduces the expression amount of GR and inhibits the mechanism of negative feedback on HPA. The lower negative feedback on HPA could lead to ketonemia. Several active ingredients of Xiaoyao San can raise the expression of GR and recover the negative feedback of HPA axis to relieve depression and illness state. In spite of the poor understanding of the current effective components in Xiaoyao San, this will be the focus of our further research. The study of Xiaoyao San could help us better understand its anti-depression mechanism and cure the patients.